High-power MEMS switch enabled by carbon-nanotube contact and shape-memory-alloy actuator - Dahmardeh, Masoud; Mohamed Ali, Mohamed Sultan; Saleh, Tanveer; Min Hian, Tee; Moghaddam, Mehran Vahdani; Nojeh, Alireza; Takahata, Kenichi (Wiley-VCH Verlag, 2013)
A forest of vertically aligned carbon nanotubes (CNTs) is integrated as an electrical contact material with a high-power, normally-open switch based on micro-electro-mechanical systems (MEMS) technology. A shape-memory-alloy (SMA) cantilever is thermally actuated to enable switching between the movable CNT forest and the copper electrode formed on the SMA. The out-of-plane SMA actuator provides high forces to enable distributed contacts with the CNT forest, achieving low contact resistances and high ON/OFF resistance ratios. The ON state of the switch shows contact resistances as low as 35Vwith a dependence on the operating current. The device operation is performed with over 5-W input powers. Long-term operation with more than 1106 switching cycles is demonstrated. The results indicate that a combination of the CNT-based contact and the SMA actuator may be a promising path to realizing reliable MEMS contact switches for high-power applications.